Salute mentale e adolescenti Intervista a Patrick McGorry - Brandizzi, Martina; Lo Cascio, Nella; Masillo, Alice; Saba, Riccardo; McGorry, Patrick (Il sogno della farfalla, 2018)
In this interview, the professional biography of Patrick McGorry was narrated. Patrick McGorry is one of the most outstanding experts in psychosis prevention worldwide. He started working at a hospital department for early psychosis in the 1980s. Struck by huge damage caused by traditional psychiatry, and supported by European and North American peers, he started to develop a new approach aimed at reducing delay in patients’ access to therapies so as to increase the possibility of cure of patients at a first psychotic event. By fighting against conservatism of traditional psychiatry and the pessimism of those who still believed in the concept of dementia praecox, he contributed to change substantially the way mental health centres for youths were structured. Today, at approximately 100 Headspace centres in Australia, free and adequate access is provided to the youths with subthreshold symptoms at a risk of developing a full-blown mental illness, who cannot accede to traditional mental health centres because they are not considered to be ill yet. With his work, McGorry placed mental health at the centre of public debate thereby contributing to changing the image of psychiatry dramatically.